IoT Based Delivery Robot with Theft Detection for Food and Goods Supply - Shankar K.; Mohan K. Raj; Gnanamurugan S.; Fayaz Begum S.; Maruthi Prasad M.; Reddy Y. Pavan Kumar (E3S Web of Conferences)
The robot employs a NODEMCU board to achieve complete capabilities through smartphone control. The robot includes a four-wheel driving system with a protective delivery area obeying only recipient authorization thus ensuring package security. An ultrasonic sensor enables the robot to move while avoiding people alongside obstacles in physical space. Through the remote camera control team members can oversee the robot’s movement path and detect any signs of attempt-ed stealing behaviour. The robot uses an audio communication system that includes a speaker and microphone for customer interaction along with features to warn recipients about its arrival and automatically trigger an alarm during theft situations.